Effect of genetic elimination of seed lipoxygenases on agronomic characteristics of soybean - Martins, Carlos Alberto Osório; Sediyama, Carlos Sigueyuki; Moreira, Maurílio Alves; Reis, Múcio Silva; Rocha, Valterley Soares; Oliveira, Maria Goreti de Almeida (Pesquisa Agropecuaria Brasileira, 2002)
<!–[if gte mso 9]> Normal 0 <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Arial Unicode MS"; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:128; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1 -369098753 63 0 4129279 0; @font-face font-family:"\@Arial Unicode MS"; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:128; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1 -369098753 63 0 4129279 0; @font-face font-family:ff3; mso-font-alt:"Times New Roman"; mso-font-charset:0; mso-generic-font-family:auto; mso-font-pitch:auto; mso-font-signature:0 0 0 0 0 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR; h1 mso-style-next:Normal; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; page-break-after:avoid; mso-outline-level:1; font-size:24.5pt; font-family:"Times New Roman"; color:black; mso-font-kerning:0pt; mso-ansi-language:PT-BR; font-weight:normal; text-decoration:underline; text-underline:single; h2 mso-style-next:Normal; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; page-break-after:avoid; mso-outline-level:2; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:PT-BR; p.MsoBodyText, li.MsoBodyText, div.MsoBodyText margin-top:11.25pt; margin-right:0cm; margin-bottom:0cm; margin-left:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; background:white; font-size:12.0pt; mso-bidi-font-size:11.5pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; color:#333333; mso-ansi-language:PT-BR; span.ff11 mso-style-name:ff11; mso-ascii-font-family:Arial; mso-hansi-font-family:Arial; mso-bidi-font-family:Arial; font-weight:normal; font-style:normal; p.plff1, li.plff1, div.plff1 mso-style-name:"pl ff1"; margin-right:0cm; mso-margin-top-alt:auto; mso-margin-bottom-alt:auto; margin-left:0cm; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Arial Unicode MS"; span.ff31 mso-style-name:ff31; mso-ascii-font-family:ff3; mso-hansi-font-family:ff3; font-weight:bold; font-style:normal; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> The genetic elimination of lipoxygenase (Lox 1, Lox 2 and Lox 3) enzymes from soybean seeds is a way to overcome the problems associated with the undesirable beany flavor of soybean seeds. Aiming at elucidating the influence of this genetic elimination on the agronomic characteristics of the soybean plants and grain yield components, the commercial variety of soybean FT-Cristalina RCH and its backcross derived lines, lacking the three lipoxygenases in the seeds (triple-null) and with these enzymes (triple-positive) were evaluated at three sowing dates. The commercial variety was more homogeneous than the lines with or without lipoxygenases, indicating the presence of significant amount of genes of the non-recurrent progenitors in the lines, mainly in the triple-null. The different sowing dates evidenced more differences among genetic materials (commercial variety, triple-null and triple-positive lines), in plant characteristics and grain yield components. The genetic elimination of lipoxygenases of the seeds did not negatively affect the agronomic characteristics of FT-Cristalina RCH soybean variety.